ФОРМУВАННЯ ТВОРЧОЇ ОСОБИСТОСТІ ДИЗАЙНЕРА ЯК КОМПОНЕНТА ДИЗАЙНЕРСЬКОЇ ОСВІТИ (Педагогіка вищої та середньої школи, 2006)
In the article the features of forming of creative personality. condition for its development as an inalienable part of designer education are examined.